Optimization of propolis ultrasound-assisted extract and identification of its phytochemical and wound healing properties - Najihah, Yusof (2023)
Natural products like propolis have captivated endless attention among researchers due to the presence of various beneficially active compounds such as phenolic acids and flavonoids and these compounds possess anti- inflammatory, anti- oxidative, anti- microbial, anti- carcinogenic, wound healing properties and many others. However, to obtain the phenolic compounds and active phytochemicals from propolis, the crude propolis is required to undergo an extraction process first. Generally, conventional extraction method (maceration) (MAE) has been the most commonly used extraction method to extract active compounds from propolis but unfortunately, the method requires ample time and energy as well as involving high amount of solvent usage. The information on the cytotoxicity effect of the usage and its potential wound healing effect is still lacking. This study was designed to compare the efficiency of maceration (MAE) with the non- conventional extraction method (ultrasonic- assisted extraction) (UAE) through kinetic and thermodynamic studies and to investigate the use Response Surface Methodology (RSM) to ultrasonic- assisted extraction on the extraction of total phenolic content (TPC) from Malaysian propolis from Geniotrigona thoracica stingless bees as well as its potential wound healing capability. Total phenolic and total flavonoid content analyses, α, α-diphenyl-β-picrylhydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS+) free radical scavenging assays and Ferric Reducing Ability of Plasma (FRAP) assay were implemented to determine the antioxidant activity of propolis extracts. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) analysis and scratch assays were done on EA.hy926 cells to study the cytotoxicity effect and potential wound healing activity of propolis extracts. The kinetics and thermodynamics results of ultrasonic-assisted extraction were; Ea; 0.032kJ/mol, ΔH#: -2.7796 to -2.4470 kJ/mol, ΔS#: ~8.22 J/kmol and ΔG#: -5559.16 to -4894.01 J, whereas, maceration’s Ea: 68.13 kJ/mol, ΔH#: 65.3160 to 65.6486 kJ/mol, ΔS#: -220.19 to -193.16 J/kmol and ΔG#: 130633.08 to 131298.25 J. The optimization resulted in TPC (coded), Y = 0.082 + 0.013X1 + 0.006114X2 + 0.007554X3 – 0.001739X1X2 – 0.00725X1X3 – 0.0006892X2X3 + 0.006103X12 – 0.001487X22 – 0.003858X32and the optimum conditions for ethanol concentration (X1) was 80%, extraction time (X2) was 25 minutes and extraction temperature (X3) was 60ºC which yielded 0.1007 ± 0.272 mg GAE/ g (experimental) and 0.1041 mg GAE/g (predicted) of TPC. The highest TPC was found from 80% ethanolic propolis extract; TPC: 8.8975 ± 0.008 mg GAE/g, and the highest TFC was found from 50% extract, which was 0.0276 ± 0.0335 mg QE/g. For the free radical scavenging activity of DPPH and ABTS+, the IC50 values were 0.0584 mg TE/ml and 0.3979 mg TE/ml, respectively. 20% ethanolic propolis extract was non-toxic to cells while 50% and 80% extracts were toxic with IC50 of 97.5 μg/ml and 58 μg/ml individually. In scratch assay, the EA.hy926 cells were treated with 20% of ethanolic propolis extracts and formed monolayers after 18 hours of incubation, whereas, the untreated wound (negative control) was completely closed after 24 hours. This study revealed that UAE was more efficient and economical than MAE in the TPC extraction from propolis, there was a synergistic effect of ethanol concentration, extraction time and extraction temperature has generated the highest TPC, propolis exhibited antioxidant activity, cytotoxicity and potential wound healing capability at a certain concentration on EA.hy926cells.